Selection and structural characterization of anti-TREM2 scFvs that reduce levels of shed ectodomain - Szykowska, A; Chen, Y; Smith, TB; Preger, C; Yang, J; Qian, D; Mukhopadhyay, SM; Wigren, E; Neame, SJ; Gräslund, S; Persson, H; Atkinson, PJ; et al. (Cell Press, 2021)
Mutations in TREM2, a receptor expressed by microglia in the brain, are associated with an increased risk of neurodegeneration, including Alzheimer's disease. Numerous studies support a role for TREM2 in sensing damaging stimuli and triggering signaling cascades necessary for neuroprotection. Despite its significant role, ligands and regulators of TREM2 activation, and the mechanisms governing TREM2-dependent responses and its cleavage from the membrane, remain poorly characterized. Here, we present phage display generated antibody single-chain variable fragments (scFvs) to human TREM2 immunoglobulin-like domain. Co-crystal structures revealed the binding of two scFvs to an epitope on the TREM2 domain distal to the putative ligand-binding site. Enhanced functional activity was observed for oligomeric scFv species, which inhibited the production of soluble TREM2 in a HEK293 cell model. We hope that detailed characterization of their epitopes and properties will facilitate the use of these renewable binders as structural and functional biology tools for TREM2 research.